THE HEALTH BELIEF MODEL OF ASTHMA CONTROL AMONG ADULT ASTHMATIC PATIENTS IN YOGYAKARTA INDONESIA - Lisa Anita Sari (Belitung Raya Foundation, Indonesia, 2018)
Background : Asthma is a chronic respiratory disease which affects daily life of people. The ultimate target of health care for adult people living with asthma is to control their asthma. It is important to keep asthma under control in order to avoid impact of uncontrolled asthma. Objective : The purpose of this study was to examine factors related to asthma control among adult asthmatic patients based on the Health Belief Model (HBM). Methods : This was a descriptive study with cross-sectional design, which conducted in Pulmonary Primary Health Center (PPHC) Yogyakarta on April 2016. There were 397 participants selected using simple random sampling. Asthma control was measured using Asthma Control Questionnaire (ACQ). The Rossenstock for Health Belief Model (HBM) was used to guide this study. Descriptive statistic was performed for data analysis. Results : Findings showed that age (p >.05), gender (p >.05), sufficiency of income (p >.05), educational level (p >.05), and occupation (p >.05) were not significantly related to asthma control. There was a significant correlation among perceived susceptibility (p <.05), perceived severity (p <.05), perceived benefit (p <.05), and perceived barrier (p <.05) with asthma control. Conclusion : It is concluded that asthma control of adult asthmatic patients is influenced by their perception of control their asthma. The study suggests that nurses in the community should increase health promotion to change health perceptions to keep asthma control status in adult asthmatic patients.